Hypo-osmotic swelling test (HOST) and its response in fresh and freezethawed semen* - Prasad, J K; Kumar, Satish; Mohan, Greesh; Shanker, Uma; Agarwal, S K (The Indian Journal of Animal Sciences, 2012)
Forty-eight ejaculates (24 each from FH and FJH crossbred bulls) were subjected to freezing and hypo-osmotic swelling test to record freezability in relation to membrane integrity of the spermatozoa. In fresh semen no significant difference between HOS-positive spermatozoa of both the crosses was found but bull variation was significant. HOS-positive sperm after freeze thawing also did not differ significantly between both the crosses, however, in FH crosses, a significant bull to bull variation was recorded. After freeze thawing the number of HOS-positive spermatozoa decreased to 30-50% and almost all the types of HOS-positive sperms were recorded. A significant positive correlation of HOS-positive sperm with mass motility, initial progressive motility, live count, total intact acrosome and sperm concentration was also found.